PENGARUH PERMAINAN TRADISIONAL HADANG TERHADAP KELINCAHAN PADA PERMAINAN BOLA VOLI - Dita Ismi Safitri (Journal of Physical Education and Sport Science, 2023)
Dita Ismi Safitri (NIM. 182223037), The importance of agility for volleyball games, so agility must be considered in students in order to achieve achievement goals in accordance with what is desired. Volleyball extracurricular students at SDN 01 Negarayu appear to have a deficiency in their agility, due to the lack of agility training carried out. The research method uses quantitative research methods with research design using One Group Pretest Posttest Design. The normality test of this data uses the Shapiro Wilk test with a significance value for the pretest and posttest data of 0.535 and 0.174 greater than 0.05, so the data is normally distributed. The significance value for Levene Statistic is 0.088 > 0.05, so it is normally distributed. Furthermore, the value of Tcount obtained is 18,410 and for Ttable is 1,771. Because the value of Tcount > Ttable, it can be said that there is an effect of traditional training on volleyball extracurricular students. Thus the obstacle training method can increase agility in extracurricular women's volleyball